Transport Matters : Why transport matters and how we can make it better - Shaw, Jon (Professor of Transport Geography); Docherty, Iain (Book collections on Project MUSE., 2019)
Comprising an innovative series of intersectional chapters, this book examines the ways that transport influences and is influenced by contemporary life in Britain and considers why we should change our attitude towards it in terms of key policy goals for a sustainable future.